Water-based chemical synthesis of low cost CIGS thin films. (October 2014) - Agegnehu, A. K.; Lin, Z.-J.; Ayele, D. W.; Su, W.-N.; Hwang, B.-J.
<x content-type="archive" xml:space="preserve">Abstract</x> Currently, the conversion efficiency of Cu(In, Ga)Se2 (CIGS) based solar cells is exceeding 20%. However, conventional vacuum based fabrication of thin film is expensive and not easy for mass production. In order to produce CIGS thin film solar cells in a cost effective way, we developed solution based synthetic method, which employs water as a solvent. In this work, we have successfully synthesised uniform copper indium gallium selenites as the amorphous precursor with nearly theoretical value of its chemical composition. The optimum reaction condition for the as prepared precursor was a temperature of 160°C and 25 min reaction time in a microwave. The precursor particles were dispersed, wet ground and coated on to the molybdenum substrate. Pure crystalline CIGS absorber layer of ∼0·5 μm was successfully grown by simultaneous annealing and selenisation of the precursor film. Sodium and antimony doping have been used to increase the grain size of the film significantly.